2015
DOI: 10.1017/jfm.2015.488
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence in a transient channel flow with a wall of pyramid roughness

Abstract: A direct numerical simulation investigation of a transient flow in a channel with a smooth top wall and a roughened bottom wall made of close-packed pyramids is presented. An initially stationary turbulent flow is accelerated rapidly to a new flow rate and the transient flow behaviour after the acceleration is studied. The equivalent roughness heights of the initial and final flows are k + s = 14.5 and 41.5, respectively. Immediately after the acceleration ends, the induced change behaves in a 'plug-flow' mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…As it is well-known that streaks are longer than wider across the logarithmic layer by a factor of 3 to 6, we can anticipate that suddenly imposed streamwise mean pressure gradients are less efficient in decreasing the Reynolds stress than their spanwise counterparts. This view is supported by the studies by He & Seddighi (2013), Seddighi et al (2015), and Mathur et al (2018), who showed that channel flows subjected to streamwise mean pressure gradients exhibit a similar, but less exacerbated, counter-intuitive response of flow consistent with the model presented here.…”
Section: Structural Modelsupporting
confidence: 87%
“…As it is well-known that streaks are longer than wider across the logarithmic layer by a factor of 3 to 6, we can anticipate that suddenly imposed streamwise mean pressure gradients are less efficient in decreasing the Reynolds stress than their spanwise counterparts. This view is supported by the studies by He & Seddighi (2013), Seddighi et al (2015), and Mathur et al (2018), who showed that channel flows subjected to streamwise mean pressure gradients exhibit a similar, but less exacerbated, counter-intuitive response of flow consistent with the model presented here.…”
Section: Structural Modelsupporting
confidence: 87%
“…Using fixed, uniform and small-scale roughness to simplify analysis of the flow, numerous studies have focused on roughness in the form of e.g. wall-mounted ribs (Leonardi et al, 2003), wavy walls (Kruse et al, 2006;Nakagawa & Hanratty, 2001 and pyramids (Seddighi et al, 2015). This assumption is however in contrast with conditions in the hydropower industry where the roughness characteristics of tunnels commonly are similar to random terrain (Perfect, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Yet to this day, a common way to model flow in hydropower tunnels in industry is to replace the natural roughness with numerical wall-roughness functions. This method relies on the conventional concept that roughness effects are confined to the inertial sublayer near the surface and have no direct effect on the outer flow [15], a theory which for some flow cases have been questioned [16] [17]. Many studies have been directed at the understanding of flow heterogeneity over rough surfaces.…”
Section: Introductionmentioning
confidence: 99%